Factors Affecting Employee Job Satisfaction at PT. Bank Perkreditan Rakyat (BPR) Hasamitra in Makassar City - Haeruddin, M. Ilham Wardhana (PT Smart Media Makassar, 2025)
The purpose of this study was to determine the factors that influence employee job satisfaction at PT. Bank Perkreditan Rakyat (BPR) Hasamitra in Makassar City. The population in this study were all employees of PT Bank Perkreditan Rakyat (BPR) Hasamitra as many as 29 people. The number of samples was 29 people using saturated sampling technique. Data collection was carried out using documentation, interviews, and questionnaires. The data analysis technique used is multiple regression analysis using Statistical Product and Service Solutions (SPSS). The results of this study indicate that job satisfaction factors consisting of supervision, operating procedures, promotion opportunities and co-workers simultaneously have a significant influence on employee job satisfaction and partially supervision factors and promotion opportunities factors have a negative and insignificant effect on job satisfaction, operating procedures factors have a positive but insignificant effect on job satisfaction and co-worker factors have a positive and significant effect on job satisfaction. The correlation coefficient of 0.581 is in the interval 0.40 - 0.5999 which shows the strength of the relationship between the independent variable and the dependent variable is moderately correlated. The coefficient of determination of 0.337 shows the independent variable to predict the dependent variable by 33.7%, the remaining 66.3% is influenced by other factors.